1998
DOI: 10.1046/j.1365-313x.1998.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of a senescence‐enhanced metallothionein gene inArabidopsisin response to isolates ofPeronospora parasiticaandPseudomonas syringae

Abstract: SummaryThe metallothionein gene, LSC54, shows increased expression during leaf senescence in Brassica napus and Arabidopsis thaliana. A number of abiotic and biotic stresses have been shown to induce senescence-like symptoms in plants and, to investigate this further, the promoter of the LSC54 gene was cloned and fused to the GUS gene and transformed into Arabidopsis. The promoter was highly induced during leaf senescence and also in response to wounding; histochemical analysis indicated that this induction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 27 publications
1
73
0
4
Order By: Relevance
“…Although the majority of expressed MT genes belong to type 2, type 1, 3 and 4 MT have also been reported to be involved in various plant processes. Transcript accumulation of type 1 MT was shown in various organs and also in response to pathogen attack (Butt et al 1998). In this study, induction of a type 1 MT was observed 12 hpi followed by a decline at 24 hpi.…”
Section: Response To Stimulus-related Genessupporting
confidence: 55%
“…Although the majority of expressed MT genes belong to type 2, type 1, 3 and 4 MT have also been reported to be involved in various plant processes. Transcript accumulation of type 1 MT was shown in various organs and also in response to pathogen attack (Butt et al 1998). In this study, induction of a type 1 MT was observed 12 hpi followed by a decline at 24 hpi.…”
Section: Response To Stimulus-related Genessupporting
confidence: 55%
“…Double mutants acd6-1 fls2, acd6-1 bak1-4, and acd6-1 mpk3 were obtained by doing crosses and screening the F2 generation for plants homozygous for acd6-1 by PCR using derived cleaved-amplified polymorphic sequence markers (Rate et al, 1999) and using the respective gene-specific primers (fls2, 59-AGGGCTTCTTACAAACCTTCG-39 and 59-CGTTGATGTTTTTGAACACCC-39; bak1-4, 59-CCTCCTATCTCTCCTA-GACCGCCATC-39 and 59-CTCTTAAACAGGAGGCAACACTTCCA-39; mpk3, 59-TGCGCTTATTGACAGAGGTAA-39 and 59-CCGTATGTTGGATTGAGT-GCT-39) and the left border primer of the T-DNA (59-ATTTTGCCGATTTCGG-AAC-39) for the second mutation. Plants were grown as described (Greenberg et al, 1994;Butt et al, 1998) in 16-h-light/8-h-dark conditions for 19 to 21 d and then harvested for various assays.…”
Section: Plant Growth Conditionsmentioning
confidence: 99%
“…Plants (Arabidopsis thaliana) were grown in growth rooms or aseptically, as described elsewhere (Greenberg et al, 1994;Butt et al, 1998), in a 16-hr-light and 8-hr-dark cycle. Pseudomonas syringae pv maculicola ES4326 and P. s. pv tomato DC3000 and its derivatives were obtained from F.M.…”
Section: Plant Growth Pathogenicity Assays Chemical Treatments Andmentioning
confidence: 99%